Teaching method for reading musical notation and sightsinging, including its application in contemporary non-tonal music - Jurie Wynand Wessels (College of Music, 2024)
Object: To suggest a method of teaching sightsinging. Objections to the Tonic Solfa System. Designed for diatonic music, does not work with non-distonic. A comparison of various fixed name system. (a) English letter names. ( b) German letter names. ( c) French solfege. ( d) Siler's Safa System. Methods used: 1. Safa or Safa and Solfa syllables. 2. Shape notes. 3. Intervals associated with objects. 4. Rhythm names. Notes to the teacher.